The genetics and breeding of the Portuguese oyster, Crassostrea angulata: lessons, experiences, and challenges in Vietnam - Thi Nhu Phuong Le; Sang Van Vu; Sarah C. Ugalde; Sankar Subramanian; Arthur Gilmour; Michael Dove; In Van Vu; Juergen Geist; Thi Nang Thu Tran; Cedric Gondro; Giang Truong Cao; Tat Thanh Le; et al. (Frontiers in Marine Science, 2023)
Aquaculture mollusc production is predominantly from Asia, with more than 80% of the total biomass produced in China. Vietnam’s annual mollusc production is growing rapidly but is comparatively small given its coastal resources. A significant challenge for future mollusc production, and oysters in particular, is the supply of high-quality spat. Most mollusc spat in Vietnam comes from local wild sources or is imported from China. Particularly in the case of oysters, where wild collection is low and importation of oyster spat into Vietnam from other jurisdictions is not controlled, supply is unreliable and presents a biosecurity risk to the industry. Controlling the life cycle in hatcheries can increase the sustainability and reliability of spat supply with the advantages of genetic enhancement in the long term. Beyond well-established selection methods based on phenotypic data for pedigreed families, the rapid development of genomic technology has enabled innovation in hatchery production based on genetic programs. This technology allows greater insight into oyster genetics in intensive aquaculture production systems. Recent reviews of selection programs demonstrate that inbreeding control via mate selection is an effective strategy for oyster species. Genetic response through combinations of individual and family-based selection can enhance morphometric traits by 10% per generation and disease resistance by 15% per generation in many aquaculture species. Genomic techniques provide information for selecting candidates at an earlier stage and improve prediction accuracy. In this paper, we review the literature on popular genomic tools and breeding techniques used for molluscs, focusing on the Portuguese oyster, Crassostrea angulata. This is to better comprehend how modern quantitative and molecular genetic technologies are being applied in mollusc breeding programs. It considers opportunities for and the feasibility of using genomic-based selection as well as the challenges that are faced in breeding programs transitioning to these new methods.